2019
DOI: 10.1002/adfm.201900516
|View full text |Cite
|
Sign up to set email alerts
|

Multistimuli Response and Polymorphism of a Novel Tetraphenylethylene Derivative

Abstract: Multi-stimuli-responsive fluorescent molecule tetraphenylethylene (TPE) derivative 1 is synthesized, which contains a TPE skeleton and peripheries of two methoxyl groups and one carboxyl group. It shows a typical aggregationinduced emission behavior and also exhibits fluorescence responses to pH change and amine vapors, and multicolored mechanochromic properties. The emission of 1 can be reversibly switched among blue (1p-f, 462 nm, Φ f = 7.4%), bright cyan (1p-h, 482 nm, Φ f = 82.3%), and yellow (1p-g, 496 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(71 citation statements)
references
References 46 publications
(49 reference statements)
0
71
0
Order By: Relevance
“…[6,[20][21][22] The term piezofluorochromica ggregation-induced emission (PAIE) was even introduced. [23] Many pure organic mechanochromic materials with AIE-activem olecules were thus reported, [24][25][26][27][28][29][30][31] along with organoboron complexes. [32,33] Regarding metal-based compounds that combine AIE and mechanochromic properties, few studies have been reported, with examplesb ased on iridium(III), [34][35][36][37][38][39] cadmium(II), [40] zinc(II), [41,42] and gold(I) [43] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[6,[20][21][22] The term piezofluorochromica ggregation-induced emission (PAIE) was even introduced. [23] Many pure organic mechanochromic materials with AIE-activem olecules were thus reported, [24][25][26][27][28][29][30][31] along with organoboron complexes. [32,33] Regarding metal-based compounds that combine AIE and mechanochromic properties, few studies have been reported, with examplesb ased on iridium(III), [34][35][36][37][38][39] cadmium(II), [40] zinc(II), [41,42] and gold(I) [43] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, crystal‐R had a much tighter packing mode than crystal‐Y. [ 21 ] The nonradiative transitions could thus be suppressed to some extent, which was in accordance with the fact that crystal‐R had a higher Φ PL than crystal‐Y. [ 22 ]…”
Section: Resultsmentioning
confidence: 67%
“…In other words, crystal-R had a much tighter packing mode than crystal-Y. [21] The nonradiative transitions could thus be suppressed to some extent, which was in accordance with the fact that crystal-R had a higher Φ PL than crystal-Y. [22] Differential scanning calorimetry (DSC) measurements were carried out to further explore the phase transition behavior.…”
Section: (5 Of 10)mentioning
confidence: 83%
“…Recent research has shown that many AIE phenomena rely on surface adsorption, self-assembly, crystallization, polymerization, etc. [23][24][25][26][27][28] Besides, some groups reported the monitoring of the transition temperature by introducing AIE units into polymer chains, which illustrated the potential application of the AIE units as uorescent probes. For example, Bao et al developed a sensitive and reliable approach for the detection of the glass transition temperature (T g ) of polymers using tetraphenylethene derivatives as uorescent sensors; 29 Yang and coworkers proposed an efficient method to measure the topology freezing transition temperature (T v ) of a vitrimer by the uorescence change in the AIE molecules; 30 Wang et al reported enhanced uorescence emission around the lower critical solution temperature (LCST) by importing the AIE property into the thermo-responsive polymer.…”
Section: Introductionmentioning
confidence: 99%